Elderly and polypharmacy: physiological and cognitive change - Rodrigues, Daniela A. (2020)
Population ageing is one of the most significant social transformations of the twenty-first century. The increase in average life expectancy was a successful challenge achieved in the modern world. However, nowadays a new challenge arises for all society: achieving a better quality of life for increasing people’s life. The comorbidities associated with ageing make elderly prone to polypharmacy. On the other hand, physiological and cognitive changes interfere with drugs’ pharmacodynamics and pharmacokinetics contributing to drug-related problems which have been reported to account for a large percentage of emergency treatment and hospitalizations of older people, increasing the costs with health in the most aged regions. In order to reduce the use of potentially inappropriate medicines in this population, strategies and tools have been developed in recent years to assess the appropriateness medication use in the elderly.